Pengaruh Penguasaan Kosakata Dan Tata Bahasa Terhadap Kemampuan Siswa Dalam Teks Recount (Survei di SMA Swasta Jakarta Timur) - Aripin, Asep Ahmad Zenal (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study aims to determine: 1) The simultaneous influence of vocabulary and grammar mastery on students' ability in recount text. 2) The influence of mastery on students' ability in recount text. 3) The influence of grammar mastery on students' ability in recount text. The method used in this study is a survey with correlational and multiple regression techniques. The population in this study were 550 students of class X SMAS Angkasa 1 Jakarta and SMAS Angkasa 2 Jakarta. The researcher determined the sample in this study with a total of 60 students taken using random sampling. Data collection techniques with multiple choices and assessment rubrics. Data analysis techniques using SPSS 22. The results of the study are 1) There is a significant influence of Vocabulary Mastery and Grammar Mastery simultaneously on the Recount Text Ability of students of Private High Schools in East Jakarta. This is evidenced by the sig value = 0.000 0.05 and F count = 64.971. 2) There is a significant influence of Vocabulary Mastery on the Recount Text Ability of students of Private High Schools in East Jakarta. This is proven by the Sig Value = 0.008 0.05 and t count = 3.823. 3) There is a significant influence of Grammar Mastery on the Recount Text Ability of Private High School Students in East Jakarta. This is proven by the Sig Value = 0.004 0.05 and t count = 3.009.